Investigation of bacterial neuraminidase inhibition of xanthones bearing geranyl and prenyl groups from Cratoxylum cochinchinense - Jeong Yoon Kim; Zuo Peng Li; Gihwan Lee; Jeong Ho Kim; Abdul Bari Shah; Yong Hyun Lee; Ki Hun Park (Frontiers in Chemistry, 2023)
Introduction: The root of Cratoxylum cochinchinense has been widely used as Chinese folk medicine to cure fevers, burns, and abdominal complications because it contains various bioactive metabolites such as xanthones, triterpenes, and flavonoids. In this study, we estimated bacterial neuraminidase inhibition with a series of xanthones from C. cochinchinense. BNA has connected to various biological functions such as pathogenic bacteria infection inflammatory process after infection and biofilm formation.Methods: The identification of xanthones (1–6) bearing geranyl and prenyl groups was established by spectroscopic data using UV, IR, NMR, and HREIMS. BNA inhibitory modes of isolated xanthones were investigated by Double-reciprocal plots. Moreover, the competitive inhibitor was evaluated the additional kinetic modes determined by kinetic parameters (k3, k4, and Kiapp). The molecular docking (MD) and molecular dynamics simulations (MDS) studies also provided the critical information regarding the role of the geranyl and prenyl groups against BNA inhibition.Results: A series of xanthones (1–6) appended prenyl and geranyl groups on the A-ring were isolated, and compounds 1–3 were shown to be new xanthones. The analogues within this series were highly inhibited with excellent affinity against bacterial neuraminidase (BNA). A subtle change in the prenyl or geranyl motif affected the inhibitory potency and behavior significantly. For example, the inhibitory potency and binding affinity resulting from the geranyl group on C4: xanthone 1 (IC50 = 0.38 μM, KA = 2.4434 × 105 L·mol−1) were 100-fold different from those of xanthone 3 (IC50 = 35.8 μM, KA = 0.0002 × 105 L·mol−1). The most potent compound 1 was identified as a competitive inhibitor which interacted with BNA under reversible slow-binding inhibition: Kiapp = 0.1440 μM, k3 = 0.1410 μM−1s−1, and k4 = 0.0203 min−1. The inhibitory potencies (IC50) were doubly confirmed by the binding affinities (KA).Discussion: This study suggests the potential of xanthones derived from C. cochinchinense as promising candidates for developing novel BNA inhibitors. Further research and exploration of these xanthones may contribute to the development of effective treatments for bacterial infections and inflammatory processes associated with BNA activity.